Effectiveness of orange fruit and dragon fruit combined with iron tablets on hemoglobin levels in pregnant women with anemia - Eliani, Eliani; Marsita, Elma; Rosita, Desy; Khasanah, Furaida (Borneo Scientific Publishing, 2025)
The prevalence of anemia among pregnant women at the Mandor Community Health Center is quite high, reaching 27.4% of 575 targets, with 147 cases of mild anemia (9-10 g/dl) and 11 cases of moderate anemia (7-8 g/dl). Preventive measures were taken pharmacologically by administering 90 Fe tablets, as well as non-pharmacologically by consuming citrus fruits or dragon fruit combined with Fe tablets. This study aimed to analyze the effectiveness of the combination of citrus fruits and Fe tablets compared to the combination of dragon fruit and Fe tablets in increasing hemoglobin levels in pregnant women with anemia at the Mandor Community Health Center. Using a quasi-experimental design with a pretest-posttest two-group design, this study involved 44 samples from a population of 158, divided into two groups of 22 respondents each for the citrus fruit and dragon fruit interventions. The analysis results showed an increase in hemoglobin levels in both groups, with a median value of 10.750-11.750 for the citrus group and 10.070-11.150 for the dragon fruit group. The Mann Whitney test produced a p-value of 0.019 (<0.05), indicating that the combination of citrus fruit and iron tablets was more effective in increasing hemoglobin levels in pregnant women with anemia than the combination of dragon fruit and iron tablets at the Mandor Community Health Center.